Numerical Study on the Spontaneous Combustion of High-density Polyethylene. (2018) - Shi, Long; Gong, Jun-hui; Huang, Dong-mei; Liu, Xuan-ya; Zhang, Guo-min
Abstract: Although non-charring polymers have been frequently utilized in the industry, public transport and buildings, their fire risk could be more serious comparing to the others such as timber fire. This is much due to the melting process in solid phase and also the high temperature and a large number of gas volatiles in gas phase. The numerical modeling of non-charring polymers could be complicated because of the difficulty in describing melting processes and in-depth radiation (for some transparent polymers). In this study, a numerical model was developed to predict the fire behaviors of a typical non-charring polymer (high-density polyethylene). The focus was on its fire behaviors under spontaneous ignition conditions, namely without the acceleration of spark plug. The model has considered both solid and gas phases, such as pyrolysis reactions, melting process, in-depth radiation, gas and liquid transportation inside the solid phase, and gas phase combustion. The numerical results for solid phase were validated by cone calorimeter experiment. For gas phase modeling, the predicted temperature and gas velocity are consistent with the major heat transfer processes.